Дослідження педагогічних підходів покращення тренувального процесу в армрестлінгу - Петренко, Володимир Олексійович; Петренко, Олександр Олексійович (Artmedia 24, Satteldorf, Germany, 2024)
Представлено дослідження, які базуються на системному аналізі, що дозволило комплексно підійти до вирішення педагогічних питань покращення тренувального процесу в армрестлінгу. Методика системного аналізу, яку використано в представлених дослідженнях, дозволила проаналізувати діючи принципи фізичної підготовки в армрестлігну з врахуванням фізіологічних можливостей спортсменів – армрестлерів. На основі проведеного аналізу сформовано комплекс силових вправ для комбінованого режиму тренування спортсменів – армрестлерів, в тому числі і спортсменів– армрестлерів з обмеженими можливостями, а саме вадами зору. Представлений напрямок дозволить покращити тренувальний процес під час підготовки до змагань і може бути доцільний під час тренування спортсменів – армрестлерів з вадами зору.

Research based on systematic analysis is presented, which allowed a comprehensive approach to solving pedagogical issues of improving the training process in arm wrestling. The method of system analysis used in the presented research made it possible to analyze the active principles of physical training in arm wrestling, taking into account the physiological capabilities of athletes - arm wrestlers. On the basis of the conducted analysis, a complex of strength exercises was formed for the combined training regime of athletes - arm wrestlers, including athletes - arm wrestlers with limited opportunities, namely visual impairments. The presented direction will make it possible to improve the training process during preparation for competitions and may be appropriate during the training of athletes - arm-wrestlers with visual impairments.
Research of pedagogical approaches to improvement training process in arm wrestling
Keywords: армрестлінг; комбінований режим; педагогічний підхід; системний аналіз; спортсмен; тренування; фізична підготовка; armwrestling; combined mode; pedagogical approach; system analysis; sportsman; training; physical training